Adenosine Concentration Determination for Tumor Microenvironment Simulation - Chun Chen; Chuanpeng Yang; Shuning Hu; Wenjie Nie; Sudan Ye; Minghao Lu; Xingjie Xu; Huajun Hu (Dose-Response)
Objectives We aimed to investigate the concentration of adenosine (ADO) in the tumor microenvironment (TME), focusing on its potential to modulate tumor cells and natural killer (NK) cells, thereby facilitating tumor immune escape. Methods In this study, an in vitro simulation system was developed to systematically evaluate the effects of ADO (0-500 μM) on the colony formation and migration capability of A549 (lung carcinoma) and A375 (melanoma) cell lines, as well as its action on NK92 cell activity, cytokine secretion, and cytotoxicity against tumor cells. Results The results showed that 50 μM ADO significantly promoted tumor cell proliferation (increasing the colony formation rate by 60%-80%) and migration (increasing the migration rate by 30%-40%), whereas high concentrations (>200 μM) exhibited an inhibitory effect. ADO suppressed NK92 cell activity in a dose-dependent manner, reducing the relative proliferation rate by 14.5% at 50 μM, significantly decreasing IFN-γ secretion (by 24% at 50 μM), and impairing the killing efficiency of A549, A375, and HepG2 cells (reducing their respective cytotoxicity by 20.3%, 22.4%, and 31.5%). Conclusion This study provides biological evidence that 50 μM represents a critical threshold concentration for TME simulation, elucidates the concentration-dependent bidirectional regulation of ADO.